Disentangling the Drivers of Diversity and Distribution of Fungal Community Composition in Wastewater Treatment Plants Across Spatial Scales - Zhang, Haihan; Feng, Ji; Chen, Shengnan; Li, Baoqin; Sekar, Raju; Zhao, Zhenfang; Jia, Jingyu; Wang, Yue; Kang, Pengliang (Frontiers in Microbiology, 2018)
Activated sludge microbial community composition is a key bio-indicator of the sustainability of wastewater treatment systems. Therefore, a thorough understanding of the activated sludge microbial community dynamics is critical for environmental engineers to effectively manage the wastewater treatment plants (WWTPs). However, fungal communities associated with activated sludge have been poorly elucidated. Here, the activated sludge fungal community in 18 geographically distributed WWTPs was determined by using Illumina sequencing. The results showed that differences in activated sludge fungal community composition were observed among all WWTPs and also between oxidation ditch and anaerobic-anoxic-aerobic (A/A/O) systems. Ascomycota was the largest phyla, followed by Basidiomycota in all samples. Sporidiobolales and Pezizales were the most abundant order in oxidation ditch and A/A/O systems, respectively. The network analysis indicated cooperative and co-occurrence interactions between fungal taxa in order to accomplish the wastewater treatment process. Hygrocybe sp., Sporobolomyces sp., Rhodotorula sp., Stemphylium sp., Parascedosporium sp., and Cylindrocarpon sp., were found to have statistically significant interactions. Redundancy analysis revealed that temperature, total phosphorus, pH, and ammonia nitrogen were significantly affected the fungal community. This study sheds light on providing the ecological characteristics of activated sludge fungal communities and useful guidance for improving wastewater treatment performance efficiency.